2014
DOI: 10.1021/bm500156z
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Fluorescence Imaging and Bimodal Phototherapy of Epidermal Cancer Cells with Biocompatible Self-Assembled Polymer Nanoparticles

Abstract: We have developed herein an engineered polymer-based nanoplatform showing the convergence of two-photon fluorescence imaging and bimodal phototherapeutic activity in a single nanostructure. It was achieved through the appropriate choice of three different components: a β-cyclodextrin-based polymer acting as a suitable carrier, a zinc phthalocyanine emitting red fluorescence simultaneously as being a singlet oxygen ((1)O2) photosensitizer, and a tailored nitroaniline derivative, functioning as a nitric oxide (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…Our recent resultsh ave shown that the PS 2,w hichi st otally aggregated and photochemically non-responsive in aqueous medium, is effectively encapsulated in al abel-free b-CD branched polymer similar to 1. [13] The encapsulation massively breaks the aggregation of 2,r estoringi ts fluorescence and capabilityt op hotogenerate 1 O 2 in cancerc ells. [13] We have also demonstrated the suitability of this polymericn anocarrier to solubilize the water-insoluble NOPD 3 and to transport it into cancer cells.…”
mentioning
confidence: 99%
“…Our recent resultsh ave shown that the PS 2,w hichi st otally aggregated and photochemically non-responsive in aqueous medium, is effectively encapsulated in al abel-free b-CD branched polymer similar to 1. [13] The encapsulation massively breaks the aggregation of 2,r estoringi ts fluorescence and capabilityt op hotogenerate 1 O 2 in cancerc ells. [13] We have also demonstrated the suitability of this polymericn anocarrier to solubilize the water-insoluble NOPD 3 and to transport it into cancer cells.…”
mentioning
confidence: 99%
“…The detailed parameters for running both of these programs are included in Supplementary Material Online File 1 available online at https://doi.org/10.1155/2017/4761962. Additionally, single-nucleotide variant calls were filtered by a variant-filter [12]. If multiple alleles were reported on one position, they were separated by vcfbreakmulti script from vcflib [13].…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, several papers describe the synthesis, characterization, and biomedical applications of different NO-releasing nanomaterials, including metallic nanoparticles, liposomes, dendrimers, silica nanoparticles, polymeric particles, carbon nanotubes, and quantum dots [17,31,[34][35][36]38,40,[42][43][44][45][46][47][48][49]. However, the use of NO-releasing nanomaterials in cancer treatment is a relatively new approach that needs to be explored further.…”
Section: No-releasing Nanomaterials Against Cancermentioning
confidence: 99%